Perturbation-Based Balance Training in Postoperative Individuals With Degenerative Cervical Myelopathy - Cheng, Yi-Shan; Chien, Andy; Lai, Dar-Ming; Lee, Ya-Yun; Cheng, Chih-Hsiu; Wang, Shwu-Fen; Chang, Ya-Ju; Wang, Jaw-Lin; Hsu, Wei-Li (Frontiers in Bioengineering and Biotechnology, 2020)
Degenerative cervical myelopathy (DCM) is a common aging condition caused by spinal cord compression. Individuals with DCM often presented with residual balance and functional impairments postoperatively. Perturbation-based balance training (PBT) has been shown to have positive effects on populations with neurological disorders but has yet to be investigated in DCM. The objective of this study was therefore to evaluate the effects of PBT on balance and functional performance in postoperative individuals with DCM. Fifteen postoperative individuals with DCM (DCM group) and 14 healthy adults (healthy control group) were recruited. The DCM group received a 4-weeks PBT using a perturbation treadmill. The outcome measures included mean velocity of center of pressure (COP) during quiet standing; center of mass (COM) variance and reaction time to balance perturbation during standing with forward and backward perturbation; gait speed during level ground walking; Timed Up and Go Test (TUG) and disability questionnaire scores including Visual Analog Scale, Neck Disability Index, and Lower Extremity Function of Japanese Orthopaedic Association Cervical Myelopathy Evaluation Questionnaire. The assessments were conducted pre- and post-training postoperatively for the DCM group but only once for the healthy control group. Significant improvements were observed in the mean velocity of COP, COM variance, reaction time, gait speed, and TUG in the DCM group. Disability questionnaire scores were not significantly different after training in DCM group. For between-group comparisons, significant differences that were observed pre-training were not observed post-training. The 4-weeks PBT is a potential rehabilitation strategy for addressing balance and functional impairment in postoperative individuals with DCM. In addition, the post-training performance in the DCM group exhibited trends comparable to those of age-matched healthy controls. Furthermore, the training regimens offer a practical reference for future studies on populations with balance disorders. Future studies complemented with neurophysiological assessments could reveal more information of the underlying mechanisms of PBT.